2022
DOI: 10.1088/1361-6595/ac4592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electric field profile on the accuracy of E-FISH measurements in ionization waves

Abstract: Electric field induced second harmonic (E-FISH) generation has emerged as a versatile tool for measuring absolute electric field strengths in time-varying, non-equilibrium plasmas and gas discharges. Yet recent work has demonstrated that the E-FISH signal, when produced with tightly focused laser beams, exhibits a strong dependence on both the length and shape of the applied electric field profile (along the axis of laser beam propagation). In this paper, we examine the effect of this dependence more meaningfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The polarization of the E-FISH signal is found to coincide with the external electric field vector, independent of the polarization of the probe beam [3,23]. However, the results from the previous two sections have indicated that both components of the E-FISH signal are affected by the probe beam polarization.…”
Section: Polarization Of the E-fish Signalmentioning
confidence: 79%
See 2 more Smart Citations
“…The polarization of the E-FISH signal is found to coincide with the external electric field vector, independent of the polarization of the probe beam [3,23]. However, the results from the previous two sections have indicated that both components of the E-FISH signal are affected by the probe beam polarization.…”
Section: Polarization Of the E-fish Signalmentioning
confidence: 79%
“…However, in order to facilitate calibration and measurement, the electric field distribution in most E-FISH measurements is spatially constructed. In single-filament streamer discharges [17,23] and diffuse discharges [9,11], the electric field distribution is symmetrical along the axis. The integral term in equation ( 9) can be rewritten as:…”
Section: Polarization Of the E-fish Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these uncertainties, we will not discuss the effects of dielectric thicknesses and pulse numbers on n e . Advanced laser diagnostics such as Thomson scattering [65] or E-FISH [66,67] can be used to reduce the uncertainties. However, stabilizing the micro discharges at one location for plasma and laser interaction is also challenging.…”
Section: Optical Emission Spectroscopy (Oes)mentioning
confidence: 99%
“…A method to measure the electric field which has become popular in recent years is Electric Field Induced Second Harmonic generation (E-FISH). However, this method suffers from complications which make it very hard to use for the quantitative determination of electric fields with unknown spatial distributions [5,9].…”
Section: Introductionmentioning
confidence: 99%